2016
DOI: 10.3390/ijms17122129
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Homer1b/c in SOD1 G93A Models of ALS: A Novel Mechanism of Neuroprotective Effect of Lithium and Valproic Acid

Abstract: Background: Mutations in the Cu/Zn superoxide dismutase (SOD1) gene have been linked to amyotrophic lateral sclerosis (ALS). However, the molecular mechanisms have not been elucidated yet. Homer family protein Homer1b/c is expressed widely in the central nervous system and plays important roles in neurological diseases. In this study, we explored whether Homer1b/c was involved in SOD1 mutation-linked ALS. Results: In vitro studies showed that the SOD1 G93A mutation induced an increase of Homer1b/c expression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
(40 reference statements)
1
11
0
Order By: Relevance
“…VPA neuroprotective properties are not exclusive to Parkinson's disease, but have been reported in several other neurodegenerative conditions and models, from Huntington's disease to amyloid beta-peptide induced neurotoxicity and amyotrophic lateral sclerosis [126,127]. Regarding the latter, in an ALS animal model, VPA was able to reduce the expression of Homer1b/c, modulating apoptosis and neuronal loss and promoting neuronal protection and survival [128]. Further studies are on the verge of assessing the clinical benefit of VPA use as a neuroprotective agent in humans.…”
Section: Neuroprotection From Neuronal Damagementioning
confidence: 91%
“…VPA neuroprotective properties are not exclusive to Parkinson's disease, but have been reported in several other neurodegenerative conditions and models, from Huntington's disease to amyloid beta-peptide induced neurotoxicity and amyotrophic lateral sclerosis [126,127]. Regarding the latter, in an ALS animal model, VPA was able to reduce the expression of Homer1b/c, modulating apoptosis and neuronal loss and promoting neuronal protection and survival [128]. Further studies are on the verge of assessing the clinical benefit of VPA use as a neuroprotective agent in humans.…”
Section: Neuroprotection From Neuronal Damagementioning
confidence: 91%
“…[50][51][52][53][54][55] Further studies revealed that only patients homozygous for C allele of UNC13A locus, which is known to be genetically linked to ALS and FTLD, [56][57][58] response to lithium therapy. 59 Cotreatment with lithium and valproic acid has also been tested in animal models 40,60 and used in a small size clinical trial in patients with sALS that revealed increased survival and signs of neuroprotection although doses used were too high and caused side-effects that forced termination of the trial. 61 Results of another clinical trial of lithium and valproic acid cotreatment (NCT03204500) are not yet published.…”
Section: Drugs Used For Treatment Of Psychiatric Disordersmentioning
confidence: 99%
“…In particular, lithium, an inhibitor of glycogen synthase kinase 3 (GSK‐3), and valproic acid, an inhibitor of histone deacetylases (HDACs), have been tested in animal models and ALS clinical trials. The rationale for testing these drugs was their neuroprotective potential, that has been linked to their ability to interfere with many pathways and processes involved in neuronal death, including excitotoxicity, 39 expression of glutamatergic postsynaptic density proteins of Homer family, 40,41 aberrant Notch signaling, 42 apoptosis, 43 endoplasmic reticulum stress (ERS), and autophagy 39,44 . Moreover, a synergistic effect of these two drugs has been demonstrated 45,46 .…”
Section: Drugs Used For Treatment Of Psychiatric Disordersmentioning
confidence: 99%
“…For example, microarray analysis of rat brain genes identified a variety of protein pathways modulated by VPA, including synaptic transmission, ion channels and transport, G-protein signaling, lipid, glucose, and amino acid metabolism, transcriptional and translational regulation, the phosphoinositol cycle, protein kinases and phosphatases, and apoptosis [ 9 ]. Du et al reported in their study that the downregulation of transient receptor potential channel 1 (TRPC1) gene expression and function in neurons may be involved in the mood-stabilizing action of VPA [ 10 ], while Jiang et al suggested that the downregulation of Homer1b/c is a potential mechanism for the neuroprotective effects of VPA and lithium [ 11 ].…”
Section: Introductionmentioning
confidence: 99%